2019
DOI: 10.1007/s00259-019-04297-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical impact of [18F]flutemetamol PET among memory clinic patients with an unclear diagnosis

Abstract: Purpose To investigate the impact of amyloid PET with [ 18 F]flutemetamol on diagnosis and treatment management in a cohort of patients attending a tertiary memory clinic in whom, despite extensive cognitive assessment including neuropsychological testing, structural imaging, CSF biomarker analysis and in some cases [ 18 F]FDG PET, the diagnosis remained unclear. Methods The study population consisted of 207 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
50
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 52 publications
5
50
1
Order By: Relevance
“…Third, we observed that although amyloid-␤ PET scans were usually requested according to the AUC, our clinical practice was not wholly covered by these criteria, as it was often driven by inconclusive CSF biomarker results. Our results support previous work that CSF biomarkers that conflict with the clinical diagnosis often lead to additional amyloid-␤ PET [12,13].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Third, we observed that although amyloid-␤ PET scans were usually requested according to the AUC, our clinical practice was not wholly covered by these criteria, as it was often driven by inconclusive CSF biomarker results. Our results support previous work that CSF biomarkers that conflict with the clinical diagnosis often lead to additional amyloid-␤ PET [12,13].…”
Section: Discussionsupporting
confidence: 91%
“…In our cohort, an amyloid-␤ PET was most often requested due to inconclusive results from the CSF biomarkers. This occurred in cases when diagnostic confidence was low due to inconclusive CSF A␤/tau status, or when a clinical diagnosis of AD was contradicted by a non-pathologic CSF analysis, which is largely in agreement with previous findings [13]. In fact, there were few patients with CSF A␤+/tau+ status in our cohort, indicating that patients with a clinical suspicion of AD supported by low A␤ 42 and high tau in the CSF analysis usually do not need further confirmation with amyloid-␤ PET.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In general, the studies have showed that the use of the Aβ-PET tracers led to a moderate to significant change in diagnosis, diagnostic confidence [140][141][142][143][144][145], and had a substantial impact on change in the treatment and management plan of AD [137,144,146]. It is likely that the new generation of Aβ-PET tracers with improved pharmacokinetics will allow for improved signal-to-noise ratio, hence will be more suitable for the quantification of disease progression and therapeutic monitoring.…”
Section: The Clinical Utility and Consequences Of Clinically Approvedmentioning
confidence: 99%